Formula of Moulding Sand, Bentonite and Portland Cement toImprove The Quality of Al-Si Cast Alloy - Andoko Andoko; Poppy Puspitasari; Avita Ayu Permanasari; Didin Zakaria Lubis (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
A binder is any material used to strengthen the bonding of moulding sand grains. The primary function of the binder is to hold the moulding sand and other materialstogether to produce high-quality casts. In this study, there were four binder compositions being tested, i.e. 5% bentonite + 5% Portland cement, 4% bentonite + 6% Portland cement, 6% bentonite + 4% Portland cement, and 7% bentonite + 3% Portland cement. Each specimen was measured for its compressive strength, shear strength, tensile strength and permeability. The highest compressive strength was obtained fromthe specimen composed of 6% bentonite+ 4% Portland cement. The highest shear strength was obtained from the moulding sand with 7% bentonite+ 3%Portland cement. The highest tensile strength was obtained fromthe specimen contained 5% bentonite+ 5% Portland cement. The specimen composed of 5% bentonite + 5% Portland cement had the lowest permeability of 131 ml/min, while that of 6% bentonite + 4% Portland cement had the highest permeability of 176 ml/min.